Analisis Tantangan Dan Peluang Kewirausahaan Industri Halal Dalam Pertumbuhan Ekonomi - Soraya Siti Rahayu; MUHAMMAD RIZKY RAMADHAN; RISKIA; GLEDI YALDES; META ANINTIA; Andika Nur Fajr (Journal of Economics and Business, 2024)
ABSTRACT Handling socio-economic problems is still the focus of attention for both the government and society, especially after the COVID-19 pandemic and the increasing number of poor people in big cities. The MSME program with a halal entrepreneurship model aims to not only focus on economic profits but also solve social problems. This research aims to determine the participation and socioeconomic impact of the MSME program with the halal entrepreneurship model in big cities, especially in culinary businesses and fashion design, crafts (handmade accessories and the provision of craft materials), as well as tour and travel. The research method used in this research is the facto exposure method. The results of the research show that the participation of halal entrepreneurial MSME actors has shown effective achievements through individual mental and emotional involvement in carrying out group activities, individual motivation in making contribution and a sense of responsibility within individuals towards group activities in achieving business. target. Apart from that, the socio-economic impact in the context of halal entrepreneurship also has an impact on capacity and independence in opening up business opportunities and employment opportunities. Research findings show the importance of government support from large cities and policies that are able to accommodate economic opportunities and represent the values ​​of halal entrepreneurship in the future in a sustainable manner. The recommendation of this research is to encourage the increase of MSMEs through the halal entrepreneurship model as an effort to solve social and economic problems, increase partnerships with larger entrepreneurs and encourage government regulations to accommodate opportunities and community participation as well as social economic impacts. entrepreneurship. Handling socio-economic problems and the increasing number of poor people in big cities is still the focus of attention for both the government and society, especially after the COVID-19 pandemic. ABSTRAK Penanganan masalah sosial ekonomi masih menjadi fokus perhatian pemerintah dan masyarakat, terutama setelah pandemi COVID-19 dan meningkatnya jumlah penduduk miskin di kota-kota besar. Program UMKM dengan model wirausaha halal bertujuan untuk tidak hanya berfokus pada keuntungan ekonomi tetapi juga menyelesaikan masalah sosial. Penelitian ini bertujuan untuk mengetahui partisipasi dan dampak sosial ekonomi dari program UMKM dengan model wirausaha halal di kota-kota besar, khususnya pada usaha kuliner dan desain fesyen, kerajinan tangan (aksesoris handmade dan penyediaan bahan kerajinan), serta tour and travel. Metode penelitian yang digunakan dalam penelitian ini adalah metode ekspos fakto. Hasil penelitian menunjukkan bahwa partisipasi pelaku UMKM wirausaha halal telah menunjukkan pencapaian yang efektif melalui keterlibatan mental dan emosional individu dalam melaksanakan kegiatan kelompok, motivasi individu dalam memberikan kontribusi dan rasa tanggung jawab dalam diri individu terhadap kegiatan kelompok dalam mencapai target usaha. Selain itu, dampak sosial ekonomi dalam konteks wirausaha halal juga berdampak pada kapasitas dan kemandirian dalam membuka peluang usaha dan kesempatan kerja. Temuan penelitian menunjukkan pentingnya dukungan pemerintah kota besar dan kebijakan yang mampu mengakomodasi peluang ekonomi dan merepresentasikan nilai-nilai wirausaha halal di masa depan secara berkelanjutan. Rekomendasi dari penelitian ini adalah mendorong peningkatan UMKM melalui model halal entrepreneurship sebagai upaya penyelesaian masalah sosial dan ekonomi, meningkatkan kemitraan dengan pengusaha yang lebih besar dan mendorong regulasi pemerintah untuk mengakomodir peluang dan partisipasi masyarakat serta dampak sosial ekonomi dari kewirausahaan. Penanganan masalah sosial ekonomi dan meningkatnya jumlah penduduk miskin di kota-kota besar masih menjadi fokus perhatian pemerintah dan masyarakat, terutama pasca pandemi COVID 19.